2021
DOI: 10.1111/edt.12675
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and opinions towards the prevention of orofacial injuries among water polo coaches in Catalonia: A cross‐sectional study

Abstract: Background/Aim Although orofacial injuries are frequent in water polo, fewer than 10% of players use mouthguards. The aim of this study was to determine the degree to which coaches and sports club managers encourage mouthguard use in water polo and to explore their opinions regarding other strategies designed to reduce the prevalence of orofacial injuries. Material and Methods This was a cross‐sectional study in which the coaches and sports club managers of 16 water polo clubs in Catalonia were invited to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…However, a lower percentage would recommend their use, and still, a lower percentage used them when they played sports themselves as athletes. Similar observations were reported in previous studies conducted in different countries and among various contact sports coaches where a mouthguard is essential as a preventive tool 7,19,21,31,32 . Speaking and breathing problems were the main reasons for not wearing a mouthguard, consistent with previous studies conducted among coaches 14,21 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, a lower percentage would recommend their use, and still, a lower percentage used them when they played sports themselves as athletes. Similar observations were reported in previous studies conducted in different countries and among various contact sports coaches where a mouthguard is essential as a preventive tool 7,19,21,31,32 . Speaking and breathing problems were the main reasons for not wearing a mouthguard, consistent with previous studies conducted among coaches 14,21 .…”
Section: Discussionsupporting
confidence: 91%
“…Similar observations were reported in previous studies conducted in different countries and among various contact sports coaches where a mouthguard is essential as a preventive tool. 7 , 19 , 21 , 31 , 32 Speaking and breathing problems were the main reasons for not wearing a mouthguard, consistent with previous studies conducted among coaches. 14 , 21 Coaches who used mouthguards as athletes and those who think it is an effective preventive tool reported that they would recommend using mouthguards among their players more than those who did not.…”
Section: Discussionsupporting
confidence: 87%
“…1 In addition, a study of rugby players reported SM use during matches but not during practice, 46 while water sports SM compliance has also been reported to be problematic. 47,48 SM compliance could also be affected by physical changes that may render SM less suitable for wear, as SM have been reported to physically deteriorate with time. 49,50 Custom SM changes involving shape and thickness have been reported midpoint during a high school football season, 51 and significant reductions in SM thickness with length increase have been reported after 2 years of field hockey use.…”
Section: Sm Compliancementioning
confidence: 99%
“…While aware of SM benefits, only 41% of participants in water polo, karate, taekwondo, and handball habitually used SM 1 . In addition, a study of rugby players reported SM use during matches but not during practice, 46 while water sports SM compliance has also been reported to be problematic 47,48 . SM compliance could also be affected by physical changes that may render SM less suitable for wear, as SM have been reported to physically deteriorate with time 49,50 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a general search in PubMed presents over 800 results when looking for the term “sports mouthguard”. Several of these studies have been published within Dental Traumatology 1–14 . The American National Standards Institute/American Dental Association has specified three main types of mouthguards as well as their desired properties such as hardness and impact absorption 15 .…”
mentioning
confidence: 99%